Measuring Risk Preferences in Rural Ethiopia : Risk Tolerance and Exogenous Income Proxies - Vieider, Ferdinand M.; Beyene, Abebe; Bluffstone, Randall; Dissanayake, Sahan; Gebreegziabher, Zenebe; Martinsson, Peter; Mekonnen, Alemu (World Bank Group, Washington, DC, 2015)
Risk-aversion has generally been found to decrease in income. This may lead one to expect that poor countries will be more risk-averse than rich countries. Recent comparative findings with students, however, suggest the opposite, giving rise to a risk-income paradox. This paper tests this paradox by measuring the risk preferences of more than 500 household heads spread over the highlands of Ethiopia and finds high degrees of risk tolerance. The paper also finds risk tolerance to increase in income proxies, thus completing the paradox. Using exogenous proxies, the paper concludes that part of the causality must run from income to risk tolerance. The findings suggest that risk preferences cannot be blamed for the failure to adopt new technologies. Alternative explanations are discussed.